THE REFLECTIONS OF THE SECOND GULF WAR ON THE IRAQI-KUWAITI RELATIONS 1990-2010 (American Journal of Research in Humanities and Social Sciences, 2025)
The Second Gulf War of 1990-1991 affected Iraqi-Kuwaiti relations, leaving behind negative reflections on the nature of the relationship between them, even after the fall of the Iraqi regime in 2003. Despite the presence of some positive stances taken by the two countries towards each other, the relationship between them after 2003 did not go well. It continued at the same pace, but was punctuated by reactions initiated by both parties that made it clear that they were unable to forget what had happened previously. Therefore, the effects of the war were difficult to overcome. In the period that followed the war until 2003, the relationship between the two neighbors was almost broken. After the termination of Sadam's ba'ath regime and until 2010, attempts floated to restore diplomacy between them, some of which ended with success, and others contributed to deepening the negative viewpoint about each other as the psychological impact left by the war still sheds its light on both the governments and people of both countries.